(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 2023)
The issue of consumer health and safety protection is essential for Federal Law 8.079/90 (Brazilian Consumer Defense Code) and its application to food supply is at the origin of protective laws to consumers, and it is appropriate to highlight the existence of a specific text published in this review by Professor João Arruda in 1934, in which he already identified the need for state intervention for consumer protection in such cases.